PEMBUATAN BIODIESEL METIL ESTER DARI MINYAK JELANTAH DAN METANOL DENGAN KATALIS ABU GOSOK - MITA SAPUTRI; FAJAR RESTUHADI; RASWEN EFENDI (Jurnal Sagu, 2016)
Biodisel methyl ester research has been used waste cooking oil and methanol with ash replenishment as acatalyst.This research was doing to saw the effect of catalyst concentration on biodiesel from used cookingoil. The research used a Completely Randomized Design with five treatments is M1 (catalyst 2 g), M2 (catalyst4 g), M3 (catalyst 6 g), M4 (catalyst 8 g) and M5 (catalyst 10 g) withing three replications. The data wereanalyzed using Analysis of Variance (ANOVA) and continued with DNMRT at 5% level. The research resultshas showed that the addition of a catalyst concentration of ash significantly (P<0,05) affected on the acidnumber, total glycerol content, density, saponification number, viscosity, iodin number, flash point and levelmethlyl ester, but did not significantly influence (P>0,05) on the water content. The best treatment is M5 withacid number 0,71 mg KOH/g, total glycerol content of 0,01%, density 0,88 g/cm3, viscosity of 47,94 cSt, iodinnumber 66,83 gI2/100, water content of 0,06%, flash point 249,33°C, saponification number154,84 mg KOH/g and levels of methyl ester 99,5%.